Refinamento de malha superficial baseado na aproximação suave da superficie do modelo - Cássia Regina Santos Nunes (2006)
The finite element method is a powerful tool for the engineering community. One of the barriers for automating finite element analysis is the automatic generation of highquality meshes. Meshes with good nodes distribution and well-shaped elements provides good system conditioning, which minimizes errors and singularities that might arise. However, most meshes can hardly be called satisfactory without any kind of post-processing to improve their qualities. The meshes representing models generated by the application of the Boolean and assembly operations to predefined primitives have a large number of badly shaped elements. The quality problem also raises in models obtained by the acquisition process, like scanning devices. This work presents an effective remeshing algorithm to improve the shape, distribution and connectivity of the surface mesh elements, while keeping the mesh geometrically close to the model surface. Our post-processing scheme applies series of local mesh modifications operators to the input mesh. The local operators are able to improve, refine and simplify the mesh. To ensure fidelity, a novel technique was developed to approximate the model surface by smooth surface patches. Since, most of the time, only the mesh configuration is available, a smooth surface approximation is evaluated by pieces from the mesh nodes. The approximation is used to drive the nodes movements and assure that they stay on top of the original model surface during the application of the local mesh modifications. Many examples are presented to illustrate the accomplished results of this work.